UPAYA MENINGKATKAN RASA PERCAYA DIRI SISWA DALAM MENGEMUKAKAN PENDAPAT MELALUI LAYANAN BIMBINGAN KELOMPOK - nurlaily, nurlaily (Jurnal Niara, 2018)
Based on the results of interviews with teachers mentors about the problems that often occur in students in SMP Negeri 21 Pekanbaru in obtaining information that: The lack of mutual understanding of students. This includes a lack of trust between students, lack of openness from students to teachers and sometimes also among fellow students so that often miscommunication among students who became one of the triggers of contention. Students are less able to express their opinions both to teachers and friends. Subjects in this study were students Class IX.1 SMP Negeri 21 Pekanbaru Lesson Year 2014-2015 with the number of students as many as 37 people. The form of research is action research counseling guidance services. The instrument of this research is data in the form of observation sheet of teacher activity and Student Self Confidence in Opinion Opinion. Based on the results of the analysis and discussion as presented in chapter IV can be concluded that with the Group Guidance Services can improve Student Confidence in Student Expose Class IX.1 SMP Negeri 21 Pekanbaru. Before the action shows Student Confidence in Student Opinion is still classified as "Less" with a score of 44.9 is at the interval of 30-49. In cycle I shows that Student Confidence in Student Opinion is still classified as "Medium" with the value of 60.0 is in the interval 50 - 69. While in the second cycle increased to 83.8 with the category "Good" is at the interval 70-89.